2017
DOI: 10.1080/17450101.2017.1330853
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and the humanities

Abstract: Mobility and the Humanities It seems that a new paradigm is being formed within the social sciences, the "new mobilities paradigm". (Sheller and Urry 2006, 207) The new mobilities paradigm seeks the fundamental recasting of social science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…Davidson's and Ewers's formulations resonate with my conception of poetics of mobility, by which I refer to the ways in which thematic treatment of mobility is reflected in the formin this case, how the generic features of the thriller in Mabanckou's novel and the uncanny qualities (as a sense of estranged familiarity and eerie repetition) of Rakotoson's novel translate the mobility theme into form. 4 By focusing on the representation and poetics of everyday urban mobility in African diasporic fiction, this article contributes to the topical endeavour of enhancing further dialogue between mobility studies and humanities (Merriman & Pearce 2017), and, in particular, to the relatively recent interest in applying mobility studies to the analysis of postcolonial fiction (Upstone 2014;Author 2017;Lagji 2018). Finally, the article contributes to 'mobilizing' literary urban studies by focusing on the representations of urban transport and mobility in the process of making meaning of the city and urban identities (see e.g.…”
Section: Concept Of 'Mobilities Of Form' and Chrismentioning
confidence: 99%
“…Davidson's and Ewers's formulations resonate with my conception of poetics of mobility, by which I refer to the ways in which thematic treatment of mobility is reflected in the formin this case, how the generic features of the thriller in Mabanckou's novel and the uncanny qualities (as a sense of estranged familiarity and eerie repetition) of Rakotoson's novel translate the mobility theme into form. 4 By focusing on the representation and poetics of everyday urban mobility in African diasporic fiction, this article contributes to the topical endeavour of enhancing further dialogue between mobility studies and humanities (Merriman & Pearce 2017), and, in particular, to the relatively recent interest in applying mobility studies to the analysis of postcolonial fiction (Upstone 2014;Author 2017;Lagji 2018). Finally, the article contributes to 'mobilizing' literary urban studies by focusing on the representations of urban transport and mobility in the process of making meaning of the city and urban identities (see e.g.…”
Section: Concept Of 'Mobilities Of Form' and Chrismentioning
confidence: 99%
“…Similarly, Anne Jensen (2011, 266) has suggested that mobile experiences and the power relations they involve work not only at the level of knowledge and rationalities but are also 'embodied through emotions, ambiences and sensations.' The focus on materialities, meanings and sensations raises the question about research ontologies and whether the study is located in the field of social sciences or humanities (Merriman and Pearce 2017). Our theoretical and methodological frame of reference places a lot of emphasis on the social sciences, but the question concerning the various modes through which individuals can experience movement and mobility in 'alternative ways' is just as relevant (Merriman and Pearce 2017).…”
Section: Studying Live-streamed Concerts Through the New Mobilities Paradigmmentioning
confidence: 99%
“…The focus on materialities, meanings and sensations raises the question about research ontologies and whether the study is located in the field of social sciences or humanities (Merriman and Pearce 2017). Our theoretical and methodological frame of reference places a lot of emphasis on the social sciences, but the question concerning the various modes through which individuals can experience movement and mobility in 'alternative ways' is just as relevant (Merriman and Pearce 2017). The concept of 'kin-aesthetics,' introduced by Peter Merriman and Lynne Pearce (2017), is especially interesting because we argue that streamed concerts were lived, appreciated and choreographed in reimagined material places through the body and bodily movements -and also through the body's inability to move.…”
Section: Studying Live-streamed Concerts Through the New Mobilities Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Whereas the concept of kinaesthesis refers to "the sense of muscular eff ort that accompanies a voluntary motion of the body," 7 the term "kinaesthetics" can be refashioned in order to highlight the aesthetic dimensions of movement as it is "enacted, felt, perceived, expressed, metered, choreographed, appreciated and desired" by embodied subjects of diff erent kinds. 8 Mobility aesthetics, then, would not just be concerned with the production, generation, or interpretation of representations of mobility. Rather, it could be seen to encompass all manner of creative processes, practices, and embodied movements that generate aesthetic aff ects and eff ects and are apprehended by embodied subjects in diff erent ways.…”
mentioning
confidence: 99%